Reconceptualizing Continuing Professional Development in Physical Education: A Systematic Review of Implementation, Mechanisms, and Pedagogical Transformation - Ilmawati, Hilda; Juliantine, Tite; Mahendra, Agus; Sucipto, Sucipto; Gustian, Uray (Physical Education Theory and Methodology, 2026)
Background. Continuing professional development (CPD) plays a critical role in improving teaching quality in physical education (PE); however, its effectiveness remains uneven and highly context-dependent. Objectives. This study aims to systematically examine the forms of implementation, outcomes, and impacts of CPD in PE, while providing a more integrated understanding of how CPD functions as a professional learning process. Materials and Methods. A systematic literature review was conducted in accordance with PRISMA guidelines, identifying 30 empirical studies published between 2015 and 2025 across major academic databases. Data were analyzed using thematic synthesis to identify patterns in implementation, duration, and outcomes. Results. The findings indicate that CPD in PE is implemented through diverse models, including workshops, professional learning communities, and practice-based collaborative approaches. However, effectiveness is not determined solely by format or duration, but by the extent to which CPD fosters sustained engagement, reflective practice, and contextual relevance. CPD contributes to improvements in teachers’ pedagogical knowledge, instructional practices, self-efficacy, and professional identity. Evidence of impact at the student and institutional levels suggests enhanced engagement, inclusivity, and learning environments, although these effects are indirect and mediated by implementation conditions. Conclusions. CPD in PE should be understood as a dynamic, multi-level professional learning process shaped by interactions among individual, social, and institutional factors. These findings highlight the need for context-responsive and sustainable CPD designs that support meaningful pedagogical transformation.